Cellulose controlled zinc oxide nanoparticles with adjustable morphology and their photocatalytic performances. (1st May 2021) - Li, Xin; Zhang, Lili; Wang, Zhiguo; Wu, Shufang; Ma, Jinxia
Highlights: The ZnO/cellulose catalyst was fabricated at different cellulose fiber sizes. The morphology of ZnO was controlled by different cellulose fiber sizes. The rational formation mechanism of ZnO sheet and flower was proposed. ZnO/NFC prepared from small size fibers exhibited best photocatalytic activity. The photodegradation products were determined by TOC and LC–MS. Abstract: The cellulose fibers with different size and aspect ratio was used as the matrix for the controllable preparation of zinc oxide (ZnO) to synthesize ZnO/cellulose composite catalyst with adjustable photocatalytic properties. The ZnO with different morphology of sphere, sheet, and flower, was in-situ synthesized on cellulose fibers by chemical deposition method, the flower-like ZnO supported on cellulose fiber exhibited the best photocatalytic activity. Furthermore, with the decrease of fiber size, the morphology of ZnO changed from most sheet to fully self-assembled flower shape, and the average thickness of nanosheets was increased. Cellulose fibers with smaller size and higher aspect ratio were more likely to form a 3D network structure with rich pores and stable mechanical properties. Significantly, with the decreasing of fiber size, ZnO/NFC has excellent photocatalytic efficiency (100 %). All ZnO/cellulose composites can be recycled more than five times.